Presence of CTAK/CCL27, MCP-3/CCL7 and LIF in human colostrum and breast milk. - Radillo, Oriano; Norcio, Alessia; Addobbati, Riccardo; Zauli, Giorgio (Cytokine, 2013)
Human colostrum and breast milk are known to contain high levels of cytokines and chemokines, which are thought to contribute to the development of the newborn. The aim of this study was to investigate the difference in the presence and levels of 21 soluble cytokines and chemokines in paired samples of human colostrum (day 2 after delivery) and breast milk (day 4-5 after delivery) by using the multiplex technology. Of the 21 cytokine investigated in 10 pairs of samples, only β-NGF was absent in both colostrum and milk, while INF-α2, SCF and TNF-β were present in colostrum but not in human milk. As a general rule, colostrum contained higher concentrations of cytokines and chemokines with respect to breast milk. The majority of cytokines, detected in colostrum alone or in colostrum and human milk (IL-1α, IL-2Rα, IL-3, IL-16, IL-18, GRO-α, HGF, IFN-α2, M-CSF, MIF, MIG, TNF-β, SDF-1α, TRAIL) have been described in previous studies, while for the first time we describe the presence of additional cytokines either in colostrum alone (SCF) or in both colostrum and breast milk (CTAK/CCL27, MCP-3/CCL7, LIF). Our data confirm and expand previous studies showing that some cytokines/chemokines, which might contribute to the development of the gastro-intestinal and nervous systems, are overexpressed in human colostrum and breast milk, and might contribute to the development of these systems.
Keywords: Adult; Chemokine CCL27; Chemokine CCL7; Chemokines; Colostrum; Cytokines; Female; Humans; Infant, Newborn; Leukemia Inhibitory Factor; Milk, Human